Impact of three rounds of mass drug administration on lymphatic filariasis in areas previously treated for onchocerciasis in Sierra Leone. - Joseph B Koroma; Santigie Sesay; Mustapha Sonnie; Mary H Hodges; Foday Sahr; Yaobi Zhang; Moses J Bockarie (Public Library of Science (PLoS), 2013)
Background 1974-2005 studies across Sierra Leone showed onchocerciasis endemicity in 12 of 14 health districts (HDs) and baseline studies 2005-2008 showed lymphatic filariasis (LF) endemicity in all 14 HDs. Three integrated annual mass drug administration (MDA) were conducted in the 12 co-endemic districts 2008-2010 with good geographic, programme and drug coverage. Midterm assessment was conducted 2011 to determine impact of these MDAs on LF in these districts. Methodology/principal findings The mf prevalence and intensity in the 12 districts were determined using the thick blood film method and results compared with baseline data from 2007-2008. Overall mf prevalence fell from 2.6% (95% CI: 2.3%-3.0%) to 0.3% (95% CI: 0.19%-0.47%), a decrease of 88.5% (p = 0.000); prevalence was 0.0% (100.0% decrease) in four districts: Bo, Moyamba, Kenema and Kono (p = 0.001, 0.025, 0.085 and 0.000 respectively); and seven districts had reductions in mf prevalence of between 70.0% and 95.0% (p = 0.000, 0.060, 0.001, 0.014, 0.000, 0.000 and 0.002 for Bombali, Bonthe, Kailahun, Kambia, Koinadugu, Port Loko and Tonkolili districts respectively). Pujehun had baseline mf prevalence of 0.0%, which was maintained. Only Bombali still had an mf prevalence ≥1.0% (1.58%, 95% CI: 0.80%-3.09%)), and this is the district that had the highest baseline mf prevalence: 6.9% (95% CI: 5.3%-8.8%). Overall arithmetic mean mf density after three MDAs was 17.59 mf/ml (95% CI: 15.64 mf/ml-19.55 mf/ml) among mf positive individuals (65.4% decrease from baseline of 50.9 mf/ml (95% CI: 40.25 mf/ml-61.62 mf/ml; p = 0.001) and 0.05 mf/ml (95% CI: 0.03 mf/ml-0.08 mf/ml) for the entire population examined (96.2% decrease from baseline of 1.32 mf/ml (95% CI: 1.00 mf/ml-1.65 mf/ml; p = 0.000)). Conclusions/significance The results show that mf prevalence decreased to <1.0% in all but one of the 12 districts after three MDAs. Overall mf density reduced by 65.0% among mf-positive individuals, and 95.8% for the entire population.